Major urogenital malformations in Nigerian children - Adeyemo, AA; Gbadegesin, RA; Omotade, OO; Asinobi, AO (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background:There is scanty data on the pattern of childhoodurogenital malformations in many resource-poorcountries, including Nigeria. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Objective:To describe the pattern of occurrence of majorurogenital malformations in children presenting in atertiary health care centre in sub Saharan Africa. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Design:Retrospective case review. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Patients:All children with major urogenital malformationspresented at the Department of Paediatrics of theUniversity College Hospital, Ibadan, a large tertiaryhealth care institution in South West Nigeria. In theperiod from July 1985 to December 1995. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Main results:A total number of 125 cases of major urogenitalmalformations were seen during the study period.The commonest of these malformations were posterior urethral valves (40.0%), hypospedias(18.4%), ambiguous external genitalia (12.8%) andectopia vesicae (11.2%).Prenatal diagnosis was rare and most patientspresented late. Mortality during first admission was14.4% (18/125), mostly accounted for by cases ofposterior urethral valves. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Posterior urethral valves accounted for the majority of major urogenital malformations seen in the setting studied. The high mortality probably reflected the severity of the lesions and late presentation of patients (which was related to the rarity of prenatal diagnosis). Increased awareness of these lesions among physicians practising in developing countries and greater use of ultrasonography in the third trimester of pregnancy may improve the prognosis by early detection and management.